STRATEGI KOMUNIKASI PERSUASIF KOMUNITAS VOLUNTEER AKUN INSTAGRAM @BANTU.IDN DALAM MENINGKATKAN KEPEDULIAN FOLLOWERS PADA KAMPUNG PEMULUNG - Ahmad Yazid Lubis; Muhammad Ilham Tri Aji Nugroho (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2026)
Social care is an important part of creating a peaceful and just society. This study aims to identify and understand the persuasive communication strategies used by the volunteer community through the Instagram account @bantu.idn to raise followers' awareness of the social conditions of the Scavenger Village community in Jakarta. The background to this research is based on the persistence of social inequality and poverty in urban areas that require public attention and participation, especially from the younger generation. Social media is used as a communication tool to build awareness, empathy, and encourage social engagement. This study uses a qualitative descriptive approach with data collection techniques in the form of content analysis of Instagram posts and in-depth interviews with the admin and followers of the @bantu.idn account. The analysis was conducted using the persuasive communication strategy theory of Melvin L. DeFleur and Sandra J. Ball-Rokeach which includes psychodynamic, sociocultural, and the meaning construction strategies. The results show that @bantu.idn consistently presents touching visual content, empathetic narratives, and participatory invitations that are relevant to the characteristics of Generation Z. This strategy was able to build social awareness, foster empathy, and encourage increased follower interaction and participation in humanitarian issues in Kampung Pemulung (Scavenger Village). Thus, Instagram has proven effective as a persuasive communication medium in increasing community social awareness. Keywords: Persuasive Communication, Social Media, Instagram, Volunteer, Social Concern